The effects of prisoner attachment to family on re-entry outcomes: a longitudinal assessment - Brunton-Smith, Ian (The British journal of criminology, 2017)
Strong family support networks are regularly identified in the search for effective inhibitors of criminal behaviour but have rarely been empirically examined in the context of the prison population. Furthermore, we know little about the factors that may weaken or indeed enhance these bonds during a prison sentence. Using data from a longitudinal survey of male prisoners in England and Wales, we address this deficit. We show that visits from parents are influential in improving prisoners’ relations with their family. Furthermore, those prisoners that experience improved family relations are significantly less likely to reoffend whilst also being more likely to find work and desist from class A drug use.